2011
DOI: 10.1097/aog.0b013e3182165ee8
|View full text |Cite
|
Sign up to set email alerts
|

Lactogenesis After Early Postpartum Use of the Contraceptive Implant

Abstract: ClinicalTrials.gov, www.clinicaltrials.gov, NCT00847587.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 22 publications
1
60
0
2
Order By: Relevance
“…There is no evidence that the use of progestogen‐containing contraceptives affects the quantity or quality of breast milk and they appear to have no deleterious effects on infant health 16, 17. Despite this, the 2010 WHO medical eligibility criteria categorised progestogen‐containing contraceptives as medical eligibility criteria category 3 (the theoretical or proven risks usually outweigh the advantages of the method) in the first four postpartum weeks in breastfeeding women, due to lack of data on possible long‐term health effects of neonatal exposure to progestogens 17, 18…”
Section: Introductionmentioning
confidence: 99%
“…There is no evidence that the use of progestogen‐containing contraceptives affects the quantity or quality of breast milk and they appear to have no deleterious effects on infant health 16, 17. Despite this, the 2010 WHO medical eligibility criteria categorised progestogen‐containing contraceptives as medical eligibility criteria category 3 (the theoretical or proven risks usually outweigh the advantages of the method) in the first four postpartum weeks in breastfeeding women, due to lack of data on possible long‐term health effects of neonatal exposure to progestogens 17, 18…”
Section: Introductionmentioning
confidence: 99%
“…Since this review was last updated in 2008 [13], four new randomized controlled trials (RCTs) [20][21][22][23] and five new observational studies were published [16,[24][25][26][27], and an additional five observational studies that were not included in the 2008 review were identified [28][29][30][31][32], for a total of eight reports of RCTs and 41 reports of nonrandomized clinical trials or observational studies for review (Table 1). These 49 articles reported on 47 different studies investigating the use of POCs in breastfeeding women and reported clinically relevant outcomes of infant growth, health or breastfeeding performance.…”
Section: Resultsmentioning
confidence: 99%
“…In total, eight studies address the effect of initiation of POCs before 6 weeks postpartum compared with later initiation, of which five are new [16,20,22,23,32]. The majority found no effect on breastfeeding or infant outcomes, although one RCT found that more women continued breastfeeding at 6 months in the later initiation group [22] and another found more infections in infants of DMPA users [32].…”
Section: Key Question Two: Early Versus Delayed Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the increased expulsion rate of 10 -27% 12 compared to interval insertion of an intra-uterine device, strong evidence exists to suggest the effectiveness in preventing unwanted pregnancy, particularly in a Medicaid population where 1 in 4 will not attend the postpartum visit. 13 Many providers at our institution felt uncomfortable offering this immediately postpartum out fear of complications such as uterine perforation. This, unfortunately, continues to be an obstacle which may be overcome through proctoring and training.…”
Section: Wvmj Oa Retrospective Study |mentioning
confidence: 99%